2023
DOI: 10.3390/su151813498
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Feasibility of Producing Polylactic Acid (PLA) Polymers Using Spent Coffee Ground

Shu Lun Mak,
Ming Yan Tanya Wu,
Wai Ying Chak
et al.

Abstract: Coffee is one of the most popular beverages in the world. Annual coffee consumption continues to increase, but at the same time, it generates a large amount of spent coffee grounds from the brewing process that give rise to environmental problems. An appropriate solution to manage these spent coffee grounds (SCGs) becomes crucial. Our project aims at discussing the feasibility of utilizing SCGs to synthesize polylactic acid (PLA) as a recycling application for SCGs. Producing PLA from SCGs offers the opportuni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…PLA is a solution to replacing fossil plastics [46]. Reviews have indicated that using spent coffee grounds as the main source for bacterial fermentation to produce lactic acid and ring-opening polymerization to produce PLA are both possible [47]. Meanwhile, the unparalleled fatigue performance exhibited by nylon renders it indispensable in manufacturing components that are subjected to rigorous wear and tear, such as high-performance gears [48,49], among various other applications.…”
Section: Introductionmentioning
confidence: 99%
“…PLA is a solution to replacing fossil plastics [46]. Reviews have indicated that using spent coffee grounds as the main source for bacterial fermentation to produce lactic acid and ring-opening polymerization to produce PLA are both possible [47]. Meanwhile, the unparalleled fatigue performance exhibited by nylon renders it indispensable in manufacturing components that are subjected to rigorous wear and tear, such as high-performance gears [48,49], among various other applications.…”
Section: Introductionmentioning
confidence: 99%
“…Adding SCGs to the soil enhances its chemical and physical properties, increasing the levels of nitrogen (N), phosphorus (P), and potassium (K). It also enhances the structural stability of the soil aggregates, water-holding capacity, and soil hydrophobicity, improving the soil organic matter content, decreasing the soil bulk density, and increasing the soil microbial diversity [1][2][3][4]. This feature makes SCGs an effective solution for various soil types that frequently exhibit a significant deficiency of organic matter, rendering them highly vulnerable to erosion, such as in the United Arab Emirates (UAE) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This creates a sense of urgency and becomes a crucial obstacle for sustainable management, necessitating inventive solutions that address environmental issues and enhance crop production quality and quantity [9,10]. This issue can be resolved by implementing a promising and encouraging strategy that focuses on repurposing different food waste materials, including SCGs, to produce organic fertilizers with fewer chemical side effects [1,2,4,6,11]. Several studies have explored this approach [11][12][13][14][15][16], demonstrating its potential to mitigate environmental impacts while improving soil health and crop yields [12,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…According to Karmee et al [14], one ton of green coffee beans can produce approximately 650 kg of SCG. It has become a significant environmental problem because coffee grounds are dumped in landfills, but SCG can also be found in streets, pavements, and riverbeds [16,17]. The huge amounts of SCG generated each year from coffee production require efficient waste management in line with stricter environmental legislative regulations.…”
Section: Introductionmentioning
confidence: 99%